Minimum inhibitory concentration of the combination of quaternary ammonium compound with ethylenediaminetetra-acetic acid (EDTA) towards hand isolated Staphylococcus Epidermidis - Maria, Dyah Ika (Universitas Padjadjaran, 2009)
The aim of this study was to determine the Minimum Inhibitory Concentration (MIC) of the combination of Quaternary ammonium compound with Ethylenediaminetetra-acetic acid (EDTA) towards hand isolated Staphylococcus epidermidis for preventing the cross infection. The Minimum Inhibitory Concentration was determined based on a serial dilution method in 1/1000, 1/2000, 1/4000, 1/8000, 1/16000, 1/32000, 1/64000, 1/128000 concentration with two repetitions. The result showed that the 1/4000 concentration of the combination of Quaternary ammonium compound with Ethylenediaminetetra-acetic acid was the MIC. In conclusion, the combination of Quaternary ammonium compound with Ethylenediaminetetra-acetic acid had an antibacterial effect towards Staphylococcus epidermidis with the MIC in 1/4000 concentration.